Rethinking reflexivity and positionality in researching happiness: Negotiating fieldwork dilemmas in Pakistan. (November 2021) - Batool, Saira; Ali, Rabia
Abstract: This paper reflexively addresses the question of positionality from the experiences of conducting a doctoral project on happiness in Pakistan. It traces the challenges encountered by a woman researcher while interviewing women and men in a gender-segregated Pakistani society. The paper highlights the dilemmas of being insider and outsider and how these categories are shifted constantly while researching women and men in a social setting. The paper argues that gender and personal experiences create power relations between the researcher and informants that may influence the research process and outcomes. Further, the nuanced experiences of the researcher in the field turn our attention to the potential challenges, pitfalls as well as opportunities for researchers to be cognizant about one's positionality. The paper concludes with recommendations for future qualitative researchers to rethink the unexpected outcomes during the research process from the onset to be able to be better prepared to deal with them. Highlights: Understanding positionality allowed to situate the researcher in the field. Women expected the researcher to agree with their anti-men views. Being a woman researcher in a masculine space was loaded with tensions and uncertainties. Men and women participants asserted power in different ways during the interviews leaving the researcher perplexed. A well trained researcher is more likely to negotiate her positionality during the research process.